Efficiency Analysis of Full Rotation Counter Flow of Shell and Tube Heat Exchanger using CFD Tool - Ramli, Muhammad Na'im; Mustaffa, Ts. Dr. Norrizal (Research Progress in Mechanical and Manufacturing Engineering, 2024)
A heat exchanger (shell and tube) is an important equipment and is often used in industries especially those involving processes. This equipment can be used for both heating and cooling systems. This research aims to investigate the correlation between the arrangement of baffles in heat exchanger design with the resultant temperature differences (delta T) and analyze the flow dynamics inherent in the full rotation cross-flow design. The configuration made in this study is a baffles arrangement that is different from the conventional segmental design. Modeling and simulation were done in Ansys DesignModeler and Ansys FLUENT. Different heat exchangers were compared which are segmental, full rotational, and helical heat exchangers. The segmental baffles were arranged in a zigzag pattern. This design will produce less heat transfer between the two mediums because recirculation zones will form in front of the baffles. The helical design could solve the issues, but the fabrication process was quite challenging. The full rotation heat exchanger design tries to combine the helical features into the segmental design, reducing recirculation zones by creating the swirl effect. The result of the full rotation configuration can reduce the negative effects of the existence of recirculation zones but cannot completely cope with them same as the helical heat exchanger. The helical has better heat transfer rate than the full rotation and the segmental heat exchanger was the least efficient.